(untitled) (Research, Society and Development, 2022)
In building intervention projects, the elaboration of the damage map, based on the identification of pathological manifestations, is crucial for the understanding of their respective causes, especially in historic buildings. So, the study of pathological manifestations becomes something vital, not only for the survival of historical patrimonies and the evolution of engineering, but also for the understanding of how the action of aggressive agents works and their negative effects on the structure and, thus, make possible the diagnosis. correct maintenance or recovery. Thus, this study aims to collect data on the pathological manifestations present on the facades of the Santuário de Nossa Senhora de Fátima church, classified as the main church outside Portugal in honor of this Saint, and to prepare the damage map from that mapping, in order to contribute to the conservation of this building. For this, the methodology consisted of a bibliographic review, selection of historical heritage and visual inspections in loco to map and photographically document the deterioration of the facades of this building. Subsequently, the cloth map was developed in order to contribute to future maintenance and restoration works of the construction under study. Based on visual inspections and on the damage map, it is possible to state that the structure, even with infiltration points caused by the presence of moisture in the balances, as there is no means of drainage for rainwater, and dirt in places of difficult access, It is not in a state of disrepair, showing good state of conservation and with periodic maintenance being carried out.